Adaptive Sustainable Reuse for Cultural Heritage: A Multiple Criteria Decision Aiding Approach Supporting Urban Development Processes - Lucia Della Spina (Sustainability, 2020)
The European Union identifies the cultural heritage of cities as the main driver of development strategies. From this perspective, adaptive reuse can play a decisive role not only in terms of increasing the life cycle of the heritage but also as an urban strategy capable of generating new economic, cultural, and social values, thus supporting innovative dynamics of local development. The aim is to propose an integrated evaluation model based on the combined use of multi-criteria techniques, which helps to classify adaptive reuse strategies of unused cultural heritage assets and supports decision-makers in the implementation of development strategies in vulnerable contexts. The case study focuses on the potential reuse of some historical fortifications located along the coasts of the Strait of Messina in Southern Italy. The results obtained show that the proposed model can be a useful decision support tool, in contexts characterized by high complexity, able to guarantee the transparency of the decision-making process, and in which it is necessary to highlight the elements that influence the dynamics of the choice for the construction of shared development strategies.